Decolonizing Nationalism: Indonesian Diaspora and the Re-Imagination of Civic Belonging in Victoria, Australia (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This article examines how the civic practices of the Indonesian diaspora in Victoria, Australia, exemplify decolonizing civic education through lived community experiences, language maintenance, and the use of urban social spaces. Drawing on a qualitative approach that integrates literature review and empirical observation, this study argues that the Indonesian diaspora performs a form of reflective and participatory citizenship that reinterprets, rather than reproduces, formal narratives of nationalism. Urban public spaces ranging from cultural gatherings to informal community interactions operate as “open citizenship classrooms” where decolonial, place-based learning emerges through collaboration, solidarity, and intercultural negotiation. The preservation of the Indonesian language and the active participation in diaspora networks demonstrate transnational civic loyalty that challenges nation-bound definitions of citizenship while fostering more inclusive and emancipatory postcolonial identities. These findings contribute to global discussions on decolonial, community-rooted civic education by illustrating how diaspora practices expand the possibilities of plural, justice-oriented citizenship.